Erupted Compound Odontoma in a Child - Ezgi Meriç (Current Research in Dental Sciences)
Odontomas are hamartomatous lesions consisting of enamel, dentin, cementum, and pulp tissue. They are slow-growing, benign tumors showing nonaggressive behavior. They can be divided into compound odontomas (CpODs) and complex odontomas (CxODs) according to the level of organization of the tissues. The radiological diagnosis of CpODs is easy due to the presence of characteristic tooth-like structures. The incidence of these hamartomatous lesions is higher in children. The majority of odontomas are asymptomatic; however, these lesions can cause impaction, delayed eruption, or even retention of deciduous teeth. Usually, they are discovered during routine radiography. This case report aims to present the clinical and radiological findings of a rarely observed CpOD in a 9-year-old boy, along with its treatment. The lesion diagnosed in the maxillary anterior region was excised under local anesthesia. In the ongoing follow-up of the patient, no anomalies were detected.